Salmonella enterica subclinical infection: bacteriological, serological, pulsed-field gel electrophoresis, and antimicrobial resistance profiles-longitudinal study in a three-site farrow-to-finish farm - Vigo, Germán Blas (2009)
The aim of this surveillance was to study both Salmonella spp. shedding patterns and the time course of serological response in farrow-to-finish reared pigs from a subclinically infected farm. Antimicrobial resistance profile, molecular subtyping, and the relationship among the isolates were determined by pulsed-field gel electrophoresis (PFGE). A farrow-to-finish farm of 6000 sows, with a history of Salmonella Typhimurium septicemia, was selected. A longitudinal bacteriological and serological study was conducted in 25 sows before farrowing (M=S1) and in 50 offspring at 21 (M=S2), 35 (M=S3), 65 (M=S4), 86 (M=S5), 128 (M=S6), and 165 (M=S7) days of age. Serum antibodies were tested using Herdcheck Swine Salmonella antibody test kit (Idexx Laboratories, ME). Bacteria were isolated from pooled fecal samples. Suspected isolates were confirmed by conventional biochemical assays, and those identified as Salmonella spp. were serotyped. A variation between seropositive percentages and positive fecal samples was observed. Serologically positive pigs decreased from S1 to S4, and subsequently increased from S4 to S7. The percentages of fecal positive culture increased from M1 to M3, and then declined in M4, increased in M5, and were negative in M6 and M7. In the study three serovars, Salmonella 3,10:e,h:-, Salmonella Muenster, and Salmonella Bovismorbificans, were identified with low pathogenicity for swine. Three multidrug resistance strains (one belonged to Salmonella 3,10:e,h:- and two belonged to Salmonella Muenster) were found. PFGE results showed three different but closely related patterns among the 13 isolates of Salmonella Bovismorbificans, and two patterns for the three Salmonella Muenster and Salmonella 3,10:e,h:- isolates. This longitudinal study established critical points of Salmonella spp. infection in the farm and the production stages, where appropriate control measures must be taken. PFGE showed clonal relationships in each serovar. Antibiotic resistance profiles should be periodically included due to public health concerns.